New approach for medial patellar ligament splitting for treatment of upward fixation of patella - EL SHERIF, M. W. (Journal of the Hellenic Veterinary Medical Society, 2018)
A new medial patellar ligament splitting technique in cattle and donkeys is presented. It has been successfully applied on thirteen alive animals affected with permanent upward fixation of patella (UFP). The technique is simple, quick and easily applicable. In contrast to other medial patellar desmotomy techniques the present approach is less invasive, the skin at the surgical site is not incised but punctured, the pericapsular fat and joint capsule are not invaded. Minimal tissue invasiveness limits the infection of surgical site, minimizes bleeding and decreases their related postoperative consequences.